A marquis in want of a wife - Allen, Louise, 1949- (Allen, Louise, 1949- Liberated ladies, 2020)
"Ross Vincent, Marquis of Cranford, with his scarred face and formidable disposition, knows he's hardly a catch. But he needs a wife to take care of his motherless son. Shy, scholarly Prudence Scott seems ideal: she has no expectation of love or passion. She'll care for his baby in return for the protection of his name. Yet seeing Prudence on their wedding day tests Ross's willpower to not take his new wife to bed..."--Back cover.